MEDIA SOSIAL SEBAGAI MEDIUM KOMUNIKASI DAKWAH - Suharto Suharto (Al-Mishbah: Jurnal Ilmu Dakwah dan Komunikasi, 2017)
Indonesia is listed as the country with the most Twitter users in the world in 2010, more precisely amounted to 20.8% of internet users in the country or about 45 million Indonesians. The users of social media use twitter as a medium of da’wah (islamic preaching). Utilizing social media as a medium of da’wah means to affirm the existence of a preacher to always preach and transmit religious messages without being constrained by space and time. With social media facilities, a preacher also can make time efficient to interact with the audiences and sort content of da’wah which is more recent and fun.